Paisaje cultural y patrimonio. Producción y transformación de las salineras de Maras, Cusco - Delgado Antezana, Sebastián (2024)
Where are the architecture and landscape compared to the mode of territorial occupation in the Tahuantinsuyo? The research analyzes the Maras salt mines based on its status as a cultural landscape.Being a case study with a historical development in which pre-inca, inca, colonial and republican occupations have overlapped, the importance of Maras is still valid given that it has maintained salt as a constitutive element. The review of the productive and constructive processes of ancestral techniques is proposed, as well as the current cultural manifestations, based on a territorial reading of the limitations and interventions to make salt a product that particularizes the human activity of settlement around the salt of Maras in Cusco.